THE DETERMINANTS OF FIRM GROWTH IN NORTHERN GHANA - Alhassan, S. (UDS International Journal of Development, 2016)
The United Nations Economic Commission for Africa (2013) argues that in order to harness Africa’s natural resources for structural transformation it is important to establish general framework conditions for structural transformation such as education, infrastructure and access to sufficiently large, regional market. This paper examines entrepreneurship in the Northern Savannah Zone of Ghana using the experience of 440 middle range entrepreneurs with focus on the factors that influence middle range entrepreneurs ability to grow. Results of in-depth interviews and regression analysis indicate that age of the entrepreneur, access to market and participation in capacity building training significantly explain the effectiveness of entrepreneurship in Northern Ghana. The paper concludes that access to market is critical in promoting entrepreneurial growth in the study area. Keywords: Entrepreneurship, Market, Northern Ghana